Physical and technical performances are not associated with tactical prominence in U14 soccer matches. Issue 4 (1st October 2016) - Clemente, Filipe Manuel; Figueiredo, António José; Martins, Fernando Manuel Lourenço; Mendes, Rui Sousa; Wong, Del P.
ABSTRACT: The aim of this study was to analyse the association between physical/technical variables and the tactical prominence variables in U14 soccer matches. Twenty-two young amateur soccer players (13.5   0.5 years old, 5.4   0.5 years of practice, 163.3   9.8 cm in body height) from two teams of the Portuguese regional league volunteered for the study. Our results showed positive and moderate correlation between dribbling test and betweenness centrality ( r  = 0.324; p  = 0.142), and negative moderate correlation between %fatigue index and betweenness centrality ( r  = −0.390; p  = 0.073). Physical and technical variables had no statistical differences among tactical positions. Nevertheless, when tactical prominence of players from four tactical positions were compared, significant differences were found in terms of degree prestige ( p  = 0.001) and degree centrality ( p  = 0.002). This pilot study did not find strong correlations between physical/technical levels and tactical prominence in soccer matches.